Acesso ao Aeroporto Internacional Tancredo Neves, em Confins, MG: uma análise da preferência dos passageiros quanto ao modo de transporte - Anna Carolina Correa Pereira (2013)
The increased use of individual instead of collective transports (IT vs. CT) has caused social, economical, and environmental costs and, therefore, calls for policies aimed at finding alternatives for transport and traffic, as well as at increasing CT attractiveness. This thesis analyzes the passengers preferences of transport mode to access the International Airport Tancredo Neves (AITN), located in Confins, a municipality 40 km from Belo Horizonte, Minas Gerais, Brazil. It complementarily investigates the attractiveness of a proposal of implementing a rail transport system connecting to the airport. Data collection consisted of a survey and the Stated Preference (SP) technique. Data analysis comprised statistic techniques (i.e., descriptive statistics, and chi-square). In total, 396 passengers filled out a questionnaire distributed in the AITN departure lounge for domestic flights in the second half of 2012. The results point out that 74% of the sample arrived at the airport by IT, which may be related to four factors: 1) aim of the travel, 2) IT characteristics that make the user have more positive feeling towards it than the CT; 3) passengers unawareness of the available public transports or biased image of a poor quality public transport; and 4) users understanding that the bus stations are not close to origin/destination. To choose the transport mode, the passengers consider safety against thief, short displacement duration, punctuality and/or reliability, and easy access as the most important criteria. The main criteria influencing their choice for that particular travel were straight displacement, punctuality and reliability, fees paid by third parties, and transport provided by third parties. The analysis of the passengers answers to a possible change from IT to collective bus transport indicates 46.6% of acceptability among participants, who pointed the following as the major attractiveness criteria for a CT: easy access, punctuality and/or reliability, and inexpensive fees. The analysis of answers concerning a possible change from the current road transport to a potential rail transport indicates that 84.1% of the sample would have this mode in consideration to reach the airport. The main attractiveness criteria underlying the choices for the rail transport would be frequency and timetable, comfort, safety, and short travel duration, and easy access. As for the preference of transport mode and potential use of a rail transport, the highest rates were found for this particular mode, that is, rail transport. However, the analysis of the stated preference indicates that the preference for the individual transport is the most representative (73% for IT against 27% for rail transport). A fine-grained SP analysis shows that short travel duration is the most valued criteria, followed by frequency and easy access. In conclusion, the research shows that the users have an interest in using the CT, the rail transport being their first choice.